Cell phone towers and house prices in New Zealand: economic effects and policy implications. Issue 1 (2014) - Olga Filippova; Michael Rehm
<x xml:space="preserve"> Abstract </x> Purpose – Global demand growth for new cell phone towers is extraordinary. However, many markets feature onerous regulation that impedes the rolling out of new infrastructure. Regulators are primarily concerned with tower aesthetics and the perceived impact on house prices. Focusing on isolating the impact of tower aesthetic, this paper aims to discover whether proximity to cell phone towers influences house prices. Design/methodology/approach – Hedonic modeling is used to measure the influence of proximity to cell phone towers on house prices in the urban area of Christchurch, New Zealand, based on 9, 715 transactions over the period from 2004 to 2010. Three functional proximity forms are tested separately. Findings – No statistically significant connection between cell phone towers and house prices was observed. Originality/value – In light of this study's results and emerging empirical evidence on the proximity‐price relationship, New Zealand's recently introduced National Environmental Standards for Telecommunication Facilities may serve as a model of public policy on tower siting for other markets.